2004
DOI: 10.1111/j.1745-3984.2004.tb01156.x
|View full text |Cite
|
Sign up to set email alerts
|

The Chain and Post‐Stratification Methods for Observed‐Score Equating: Their Relationship to Population Invariance

Abstract: The Norz-Equivalent-groups Anchor Test (NEAT) design has been in wide use since at least the early 1940s. It involves two populations of test takers, P and Q, and makes use of an anchor test to link them. Two linking methods used for NEAT designs ure those ( a ) based on chain quating and (b) that use the anchor test to post-strati& the distributions of the two operational test scores to a common population (i.e., Tucker equating and frequency estimation). We show that, under digwent sets of assumptions, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(125 citation statements)
references
References 16 publications
(20 reference statements)
0
125
0
Order By: Relevance
“…The partition of T is determined by the weight w (see Angoff, 1971Angoff, /1984Kolen & Brennan, 2004;or von Davier et al, 2004a, for a discussion of the target population in the NEAT design and of the role of the weights).…”
Section: Neat Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The partition of T is determined by the weight w (see Angoff, 1971Angoff, /1984Kolen & Brennan, 2004;or von Davier et al, 2004a, for a discussion of the target population in the NEAT design and of the role of the weights).…”
Section: Neat Designmentioning
confidence: 99%
“…Here we give a brief outline of the KE method of observed-score test equating (von Davier et al, 2004a). The KE method is discussed in detail in von Davier et al (2004b) for all of the standard equating designs.…”
Section: Appendix a An Outline Of Kementioning
confidence: 99%
See 1 more Smart Citation
“…Harris and Kolen (1990) suggested that the PSE and the IRT OSE methods have superior theoretical underpinnings compared to the CE method while the latter method requires the least amount of computation. von Davier, Holland, and Thayer (2004a) provided some theoretical analyses of the PSE and CE methods and showed that they may both be interpreted as examples of OSE methods and that they can provide identical results under special conditions.…”
Section: Tablementioning
confidence: 99%
“…von Davier, Holland, and Thayer (2004) defined the RMSD for the anchor test or NEAT data-collection design, and Holland (2003) defined the REMSD. The REMSD index was used to obtain a single value summarizing the values of RMSD(x) over the distribution of x in the total group.…”
Section: Deviance Measuresmentioning
confidence: 99%